UNDERSTANDING PUBLIC HEALTH PROFESSIONALS: THEIR ROLES, SIGNIFICANCE, AND CHALLENGES - Tripković, Katica (Srpski medicinski časopis Lekarske komore, 2024)
The dramatic progress in public health throughout the 20th century, including the extension of life expectancy, enhancement of quality of life, and significant reductions in infant and child mortality rates, as well as the successful reduction and eradication of some infectious diseases, could not have been achieved without public health professionals responsible for the management, coordination, and provision of essential public health services. Public health systems in countries around the world, including the Republic of Serbia, are "chronically" underinvested, and face difficulties in ensuring an adequate number and appropriate distribution of qualified public health workers. Numerous challenges related to the public health workforce can be classified into several groups: social (aging workers, the profession’s lack of appeal, diminished morale and motivation, retention challenges); technological (the diverse array of education and training options, scarce opportunities for professional development); economic (insufficient financing and low salaries); environmental (antibiotic resistance, pollution, food safety, climate change, urbanization); political (lack of prominence on the agendas of political leaders, lack of legal frameworks for workforce development); and legal and ethical (absence of a well-defined ethical framework in public health). To deliver high-quality public health services, mitigate health disparities, and effectively tackle emerging health crises, enhancing the capabilities of a skilled and competent workforce is imperative. This involves gaining a comprehensive understanding of the interests and needs of public health professionals, implementing strategic succession planning, optimizing recruitment and retention of workers, and ensuring more efficient use of resources. A thorough examination of public health personnel management, together with the development of strategic and operational personnel policies within the healthcare system of the Republic of Serbia, is necessary for effectively addressing the demands posed by crises such as the outbreak of a novel infectious disease pandemic.
Keywords: public health; essential public health function; public health professionals; the Republic of Serbia